Naturalitas Islamisasi Ilmu Pengetahuan di Lembaga Pendidikan Islam - Andarwati, Andarwati (UIN Maulana Malik Ibrahim Malang, 2002)
The emergence of the concept of Islamization of science has invited much attention from various social circles, including those from Islamic educational institutions. Basically education aims to lift human dignity through a process in the form of transfer of knowledge and transfer of values. Al Faruqi demonstrates the demands of competence complexity in order to meet the criteria of educational standards of eligibility in the Islamization of science. It was concluded that for Islamic educational institution, Islamization of science is a requirement because the substance of learning is expected to produce human with intellectual and moral quality. This will be a preventative effort against intellectual bias. The formulation of the substance and practice of education based on Islamization of science is a potential challenge as it requires multi-capable and multi-skill educators. All of them have to rely on the elements of aqidah and tawhid derived from Al Quran and Hadith. In addition, educators are expected to combine those elements integrally and holistically. Munculnya konsep Islamisasi ilmu pengetahuan telah mengundang banyak perhatian dari berbagai kalangan sosial, termasuk dari kelompok praktikan lembaga pendidikan Islam. Pada dasarnya pendidikan bertujuan untuk mengangkat harkat dan martabat manusia melalui suatu proses dalam bentuk transfer pengetahuan dan transfer nilai. Al Faruqi menunjukkan adanya tuntutan kompleksitas kompetensi untuk dapat memenuhi kriteria standar kelayakan pendidik dalam Islamisasi ilmu pengetahuan. Disimpulkan bahwa bagi lembaga pendidikan Islam, Islamisasi ilmu pengetahuan adalah suatu kebutuhan karena dari substansi pembelajarannya diharapkan dapat mencetak manusia yang memiliki kualitas intelektual dan moral. Ini akan menjadi upaya preventif terhadap bias intelektual. Perumusan substansi dan praktek pendidikan berbasis Islamisasi ilmu pengetahuan ini menjadu suatu tantangan yang potensial karena menuntut pendidik memliki multi kapabilitas dan multi skill. Kesemuanya harus bertumpu pada unsur-unsur akidah dan tauhid yang bersumber dari Al Quran dan Hadits. Selain itu pendidik diharapkan mampu memadukan unsur-unsut tersebut secara integral dan holistik.